Effect of rhBMP-2 applied with a 3D-printed titanium implant on new bone formation in rabbit calvarium - Ryu, Jaeyoung; Kang, Hyo-Sun; Kang, Byung-Hun; Jung, Seunggon; Kook, Min-Suk; Oh, Hee-Kyun; Jung, Ji-Yeon; Park, Hong-Ju (Journal of Applied Oral Science, 2022)
Objective: This study sought to compare the biocompatibility of a three-dimensional (3D)-printed titanium implant with a conventional machined titanium product, as well as the effect of such implant applied with recombinant human Bone Morphogenetic Protein Type 2 (rhBMP-2) for guided bone regeneration. Methodology: Disk-shaped titanium specimens fabricated either by the conventional machining technique or by the 3D-printing technique were compared by MC3T3-E1 cells cytotoxicity assay. New bone formation was evaluated using a rapid prototype titanium cap applied to the calvaria of 10 rabbits, which were divided into two groups: one including an atelopeptide collagen plug on one side of the cap (group I) and the other including a plug with rhBMP-2 on the other side (group II). At six and 12 weeks after euthanasia, rabbits calvaria underwent morphometric analysis through radiological and histological examination. Results: Through the cytotoxicity assay, we identified a significantly higher number of MC3T3-E1 cells in the 3D-printed specimen when compared to the machined specimen after 48 hours of culture. Moreover, morphometric analysis indicated significantly greater bone formation at week 12 on the side where rhBMP-2 was applied when evaluating the upper portion immediately below the ca p. Conclusion: The results suggest that 3D-printed titanium implant applied with rhBMP-2 enables new bone formation.